MULTI-OBJECTIVE INVENTORY AND ROUTING MODEL FOR A MULTI-PRODUCT AND MULTI-PERIOD PROBLEM OF VETERINARY DRUGS - Farajzadeh Bardeji, Saeideh; Fakoor Saghih, Amir mohammad; Mirghaderi, Seyed-Hadi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In this study, a multi-objective, multi-product, and multi-period inventory management and routing model was designed for perishable products with a focus on veterinary drugs. The proposed model is a four-objective model to achieve a balance between the costs of drug distribution. The first and second objective functions are related to inventory management, covering inventory costs and demand forecast error, respectively. The third and fourth objective functions involve routing to minimize the transportation costs and greenhouse gas emissions, respectively. Data on three types of drugs were collected for 25 periods (weeks) from one drug distribution center and nine pharmacies in Iran. Non-dominated Sorting Genetic Algorithm-II was employed to find a satisfactory solution. The meta-heuristic method was combined with a Multi-layer Perceptron artificial neural network algorithm to forecast the demand. The model was implemented in MATLAB software. The results show the ability of the proposed model and algorithm to find high-quality solutions.